Study on the depth and pattern of floor failure in closely spaced bifurcated coal seams - LIANG Bing; CHEN Xintao (Gong-kuang zidonghua, 2025)
At present, most existing formulas for calculating floor failure depth are applicable to specific floor structures. Due to the complex geological characteristics of bifurcated coal seams, the variable relative dip angles and spacing between the upper and lower seams lead to a floor structure that differs significantly from those considered in previous studies, making it difficult to directly apply existing formulas to calculate the floor failure depth. To address this issue, this study took the 3-1 bifurcated coal seam in Holuowan Coal Mine as the engineering background and derived the theoretical solutions for the maximum failure depth under three failure scenarios of closely spaced bifurcated coal seams, based on the plastic slip line field theory for a single rock layer. Numerical simulations were conducted to obtain the evolution pattern of the plastic zone and the failure depth of the floor during mining. Water injection tests were employed to measure the actual failure depth of the floor in the working face. Theoretical analysis results showed that the position of the rotation center of the plastic slip line field varied with the lithology of the floor, leading to a sharp increase followed by a gradual decrease in the floor failure depth, which was calculated to be 13.30-17.62 m. Numerical simulation results indicated that shear failure was the dominant mode, and the failure zone extended from the mudstone layer to the lower 3-1 coal seam and the sandy mudstone layer. Variations in the coal-rock structure of the floor led to changes in the failure depth, ranging from 12.36 to 16.53 m, showing a similar trend to the theoretical analysis. Field measurement results showed significant changes in water loss from borehole injection before and after mining, indicating well-developed fractures in the floor strata, with a failure depth of 13.52-17.20 m. Based on the failure conditions of the floor beneath the upper 3-1 coal seam, the study classified the roof of the lower 3-1 coal seam, and pre-control strategies were proposed to ensure safe mining of the coal seam. The field measurements verified the practicality of the plastic slip line field model for bifurcated coal seam floors.